From home to homelessness: A reflection on Nora’s possible post-departure feminist life in A Doll’s House by Henrik Ibsen - Md. Abu Saleh Nizam Uddin (EduLite: Journal of English Education, Literature and Culture, 2022)
In Henrik Ibsen’s A Doll’s House, Nora’s departure from home being hurt by her husband’s behavior appears to be the most important event of the drama igniting so far a wide critical parlances of Feminist array that appreciate the departure as Nora’s freedom from male-dominated society. But Nora’s success in having a home of comfort and happiness in her post-departure future life in Feminist world deserves critical attention too. We may posit Nora will shift to a Feminist world considering the departure as the manifestation of her newly imbibed Feminist spirit because the first wave Feminism of her time is either indifferent about or antagonistic to family life by being politics-centric. However, when Nora has within her a woman’s indispensable family-centric female construction to face nonfamilial politics-centric first wave feminism, she is sure to find no home in that Feminist world. Thus, this paper aims at examining how Nora, with her declared departure from home, is going to shift to the world of first wave Feminism which, by being nonfamilial and politics-centric, works against the very family-centric construction of Nora’s female construction and offers homelessness to her.